Hochschild (Co)Homology and Applications - Keller, Bernhard (2024)
In 1945 Gerhard Hochschild published On the cohomology groups of an associative algebra in the Annals of Mathematics and thereby created what is now called Hochschild theory. The subject not only provides interesting homological invariants; it also serves as a link connecting algebra, topology, and geometry. The focus of the meeting was on recent developments, for instance in the study of singularities, deformations, and representations.